PERAN FOTOGRAFER SEBAGAI AKTOR GERAKAN SOSIAL LINGKUNGAN HUTAN BAKAU DI DENPASAR SELATAN - Deviantari, I Gusti Agung Istri; Ranteallo, Ikma Citra; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
Abstract The aquaculture industry of mangrove forests is using for economic welfare. Mangrove ecosystems, especially in Taman Wisata Hutan Raya Ngurai Rai, Denpasar Selatan, are rapidly declining by illegal logging and wastes. This research identified the roles of photographers as environmental social movement in protecting deforestation. Based on a qualitative exploratory research, the ecological theory of the city by Robert E. Park, and Roland Barthes’ semiotic analysis, I observed and interview 19 informants. The results of this study argued that the photographers mobilization efforts to address youth engangement in environmental campaigns by shared photographs of deforestation of mangroves in social media. They also asked non-government organizations and local government for joining and involving in these campaigns. Keywords: photographer, mangrove, forest, environmental social movement, social media